Synthesis New Benzimidazole Derivatives as Antibacterial (Journal of Pharmaceutical Negative Results, 2022)
N-substituted alkylbenzimidazole derivatives connected to 1,2,3-triazole through methlene linkers (tb1, tb2, tb3, tb4 and tb5) were prepared and designed with the goal of estimating their anti-organism activity such as anti-bacterial activity. FTIR and NMR spectroscopies were used to analyzed the prepared compounds. The biological potential of these substances was examined for antibacterial activity against tow type of microorganisms, the first [gram-negative (Escherichia Coli)] and the second [gram-positive (Staphylococcus Aureus)]. Compared with Gramnegative bacteria, all compounds showed a strong effect against Gram-positive bacteria.